2002
DOI: 10.1038/sj.bjc.6600433
|View full text |Cite
|
Sign up to set email alerts
|

Identical chemotherapy schedules given on and off trial protocol in small cell lung cancer response and survival results

Abstract: Patients who are treated within clinical trials may have a survival benefit dependent on being a trial participant. A number of factors may produce such beneficial outcome including more rigorous adherence to a peer reviewed trial protocol, management by an experienced treatment team, being treated in a specialist centre etc. The current investigation compared patients treated on and off trial with the same standard arm treatment regimen. The results could then be interpreted without the confounding factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…This approach in clinical trials provides greater uniformity and quality of treatment compared with treatment of the general patient population and is known to enhance outcomes. [10][11][12][13] In the book, "Checklist Manifesto," Gawande 14 describes how faulty memory and distraction can lead to errors in achieving complex tasks for all-or-none processes: preparing an airplane for takeoff, or evaluating a sick person in the emergency room. Checklists provide protection against such failures by providing process verification and instilling discipline to improve performance.…”
Section: Introductionmentioning
confidence: 99%
“…This approach in clinical trials provides greater uniformity and quality of treatment compared with treatment of the general patient population and is known to enhance outcomes. [10][11][12][13] In the book, "Checklist Manifesto," Gawande 14 describes how faulty memory and distraction can lead to errors in achieving complex tasks for all-or-none processes: preparing an airplane for takeoff, or evaluating a sick person in the emergency room. Checklists provide protection against such failures by providing process verification and instilling discipline to improve performance.…”
Section: Introductionmentioning
confidence: 99%
“…Few clinical trials have included such patients. In contrast to previous findings, a recent study demonstrated that the survival of small cell lung cancer patients receiving the same chemotherapy regimen, centralized treatment, and rigorous adherence to a defined protocol was not different from the survivals of patients treated in a clinical trial [24]. Recently, a retrospective assessment of data from the SEER tumor registry clearly showed that chemotherapy for 6232 elderly metastatic NSCLC patients was as effective as that in randomized trials with mostly younger, highly selected patients [25].…”
Section: Discussionmentioning
confidence: 83%
“…Its appointed members must have a particular interest in research, be willing to work extra hours to run the trial, and be prepared to attend study meetings within the team and other institutions. Thus, trial centers develop distinct expertise and high standards of care which nontrial patients at the same institution can profit from [14]. Until more convincing evidence is available for trial effects, we will suggest the quality of care even for patients outside a study protocol is better in trial centers than in nontrial centers.…”
Section: Introductionmentioning
confidence: 99%